Doppler frequency-code phase division multiple access technique for LEO navigation signals - Sixin, Wang; Xiaomei, Tang; Xiaohui, Liu; Wang, Feixue; Zhuang, Zhaowen (GPS solutions, 2022)
It is an important development direction to take advantage of low-earth-orbit (LEO) satellites by establishing a LEO satellite navigation system as a supplement to Global Navigation Satellite Systems in the future. On account of the fast motion of LEO satellites, there is a significant and fast change in the Doppler frequency of LEO navigation signals. Since a LEO navigation system usually consists of a large number of satellites, the search range of carrier frequencies and satellite numbers is correspondingly large in the signal acquisition process. Adopting the traditional code division multiple access (CDMA) technique will bring extremely high computational complexity to the acquisition process of LEO navigation signals, which leads to a much longer acquisition time. Considering the characteristics of LEO navigation signals, we proposed a Doppler Frequency-Code Phase Division Multiple Access (DFCP-DMA) technique in order to achieve a fast acquisition of LEO navigation signals. Because the motion of LEO satellites is fast, Doppler frequencies and code phases of LEO navigation signals arriving at the receiver differ significantly. Thus, receivers can distinguish LEO navigation signals by multiple combinations of different Doppler frequencies and code phases acquired. To decrease the acquisition complexity, all LEO satellites broadcast spread-spectrum navigation signals modulated by the same spreading code in DFCP-DMA, and receivers can acquire all navigation signals using only this spreading code. Theoretical analysis and simulation results show that, compared with CDMA, DFCP-DMA can significantly reduce the acquisition complexity without any loss in the acquisition sensitivity, which can shorten the acquisition time to 1/ M , where M is the number of satellites. There is a high application prospect for DFCP-DMA in future LEO navigation systems.